Factors Affecting Seed Germination and Establishment of an Efficient Germination Method in Sugar Pine (Pinus lambertiana Dougl.) - Xiuli Shen; Myeong-Je Cho (HortScience, 2021)
Mature sugar pine (Pinus lambertiana Dougl.) trees produce large amounts of viable seeds but have seed dormancy. In this study, we used three sugar pine genotypes, 8877, 9306, and 9375, to test seed germination response. Seed germination from local sources varied greatly, and germination percentages were poor. There was a large variation in seed size and seed weight among the genotypes. Seeds of 9375 and 9306 were significantly larger and heavier (30.7 and 28.8 g/100 seeds, respectively) than 8877 (23.6 g/100 seeds). Three types of seeds—intact seeds, hulled seeds, and naked embryos—were examined for germination. Intact seeds failed to germinate due to the physical restraint and water impermeability of the seed. Chemical scarification with 5 m hydrochloric acid and 5 m sodium hydroxide did not soften the hard seedcoat and also failed to induce any germination of intact seeds. Hulled seeds resulted in an extremely low germination percentage (≤5%) with abnormal seedling development even though the endosperm was water permeable. Germination of the hulled seeds was not increased by adding 1 mg·L−1 gibberellic acid to the culture medium. Artificial opening of the hulled seeds created by longitudinal or horizontal cuts on the endosperm after removal of the seedcoat to avoid physical restraint and allow air exchange also failed to improve germination, indicating that inhibitors related to germination were present in the endosperm. However, naked embryos of all three genotypes germinated rapidly and uniformly with 70% to 95% germination percentage regardless of cold stratification treatment. Our data indicate that sugar pine seeds from the current source did not have physiological dormancy of embryos themselves, but dormancy was imposed by the seedcoat and endosperm. Using the naked embryos as donor explants, we have successfully established an efficient in vitro culture system. The protocol described here can be applied for the tissue culture and genetic transformation of sugar pine.